2011
DOI: 10.1016/j.ijdevneu.2011.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Long‐lasting effects of perinatal asphyxia on exploration, memory and incentive downshift

Abstract: a b s t r a c tPerinatal asphyxia remains as one of the most important causes of death and disability in children, without an effective treatment. Moreover, little is known about the long-lasting behavioral consequences of asphyxia at birth. Therefore, the main aim of the present study was to investigate the motor, emotional and cognitive functions of adult asphyctic rats. Experimental subjects consisted of rats born vaginally (CTL), by cesarean section (C+), or by cesarean section following 19 min of asphyxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 68 publications
4
47
2
3
Order By: Relevance
“…The authors observed a deficit in exploration of new environments and spatial reference and working memory impairments in PA rats. Finally, when animals were downshifted from a 32% to a 4% sucrose solution, an attenuated suppression of consummatory behavior was observed in PA rats (Galeano et al, 2011). Despite of these behavioural impairment, neurological motor conditions were comparable to those of normoxic animals, in agreement with results obtained by Hoeger et al (2006).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The authors observed a deficit in exploration of new environments and spatial reference and working memory impairments in PA rats. Finally, when animals were downshifted from a 32% to a 4% sucrose solution, an attenuated suppression of consummatory behavior was observed in PA rats (Galeano et al, 2011). Despite of these behavioural impairment, neurological motor conditions were comparable to those of normoxic animals, in agreement with results obtained by Hoeger et al (2006).…”
Section: Discussionsupporting
confidence: 86%
“…including our group (Galeano et al, 2011). Galeanoís work, in particular, investigated the motor, emotional and cognitive functions of adult (three month old) asphyctic rats.…”
Section: Discussionmentioning
confidence: 99%
“…The apparatus used was previously described in detail by Galeano et al (2011). Briefly, it consisted of a circular galvanized steel pool (180 cm in diameter and 60 cm in height), painted black, filled with water at 22 ± 1°C to a depth of 36–40 cm, and imaginarily divided into four quadrants: North (N), East (E), South (S), and West (W).…”
Section: Methodsmentioning
confidence: 99%
“…Its long-lasting effects include behavioral and cognitive alterations, such as spatial memory and learning deficits, among others (Galeano, Blanco Calvo et al 2011;Cooper, Gadian et al 2013;Galeano, Blanco et al 2014;Takada, dos Santos Haemmerle et al 2015). The developing brain is extremely sensitive to reduction in oxygen supply and the hippocampus, a key region related to learning and memory, is one of the most vulnerable regions of the anoxic brain (Buwalda, Nyakas et al 1995;Vexler and Ferriero 2001;Peterson, Larson et al 2012;Takada, dos Santos Haemmerle et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In rodents, the most frequently used are the Rice-Vannucci hypoxia-ischemia (Rice, Vannucci et al 1981) and the perinatal asphyxia models (Bjelke, Andersson et al 1991). The first is induced unilaterally in 7-day-old rats, and the latter consisted by the immersion of uterus containing the ready-to-deliver fetuses in saline at 37 °C for 19-20 minutes (Morales, Fiedler et al 2008;Galeano, Blanco Calvo et al 2011). The neonatal anoxia model was first described by Dell'Anna and colleagues (Dell'Anna, Calzolari et al 1991) and was modified and validated by our group (Takada, Sampaio et al 2011), which consists in the exposure of 30-hours-old rats to 100% nitrogen gas during 25 minutes at 37 °C.…”
Section: Introductionmentioning
confidence: 99%